Effect of Calcium Chloride as a Crosslinking Agent in the Fabrication of Alginate/Beeswax Biofilm - MOHD SABIRIN, MOHAMAD HASHIM (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Brown algae are the source of alginate, a form of polysaccharide that is non-toxic, biocompatible, and biodegradable. Calcium chloride, a known crosslinking agent of alginate is assumed to act as complexing carboxylate anions of alginate by its bivalent calcium iron. Beeswax has a lot of medicinal promise when it comes to the treatment of wounds. Alginate biofilm's ability to heal wounds will be enhanced even more due to the special properties of beeswax. The solution casting technique was employed to create the alginate and beeswax biofilm that was used in this investigation. This technique allowed the amount of beeswax to be modified from 1 to 5 grammes. Following that, the calcium chloride was sprayed onto the biofilm at concentrations of 0.5w/v%, 1.0w/v%, and 1.5w/v% to act as a crosslinking agent. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), contact angle measurement of surface-wetting, and atomic force microscopy (AFM) were used to characterise the alginate/beeswax biofilm surface roughness. The microstructure that is shown by SEM demonstrates that the biofilm changes from having a reasonably smooth surface to having a rough structure when beeswax is added. Alginate and beeswax belong to the same functional group, which was made clear by the FTIR research.. The hydrophilic properties of the alginate molecule were precisely targeted by modifications to the molecule. The surface roughness of the alginate/beeswax biofilm increased, according to AFM data, with increasing amount of beeswax.